Femoral radiographic indices for pre-operative osteoporosis screening in postmenopausal female patients undergoing total hip arthroplasty for osteoarthritis - Masanori Nishi; Yasushi Yoshikawa; Yuki Usui; Hajime Nishida; Shota Nakamura; Koichiro Tashiro; Yoshifumi Kudo (PLoS ONE, 2026)
The purpose of this study was to investigate the correlation between femoral morphological indices from anteroposterior hip radiographs and dual-energy X-ray absorptiometry-assessed bone mineral density in postmenopausal female patients undergoing primary total hip arthroplasty for hip osteoarthritis. We also evaluated the impact of hip deformity on these correlations and the diagnostic cut-off values for osteoporosis. This retrospective study, conducted at a single institute (February 2018 to July 2024), reviewed the data of postmenopausal patients (>50 years old) with hip osteoarthritis who underwent total hip arthroplasty. Patients with a history of hip surgical procedures, infection, metabolic bone disease, or inadequate imaging findings were excluded. Dual-energy X-ray absorptiometry was used to assess bone mineral density at the femoral neck, total hip, lumbar spine, and distal radius. Five femoral indices were measured: the canal-to-calcar ratio, canal flare index, cortical thickness index, canal diaphysis ratio, and canal bone area ratio. Analyses included Pearson’s correlation and receiver operating characteristic curve analysis. Moderate correlations were observed between total hip bone mineral density and indices in 95 hip osteoarthritic joints (all Tönnis grade 3) and 86 normal joints. The canal bone area ratio had the strongest correlation (hip osteoarthritis: r = −0.61; normal: r = −0.62; p < 0.01). Receiver operating characteristic analysis produced area under the curve values of 0.75 (cutoff: 0.47; p < 0.01) for hip osteoarthritis and 0.74 (cutoff: 0.49; p < 0.01) for normal hips. Femoral indices, particularly the canal bone area ratio, cortical thickness index and canal diaphysis ratio, moderately correlated with total hip bone mineral density even in patients with hip osteoarthritis and served as simple and effective screening tools for osteoporosis when pre-operative dual-energy X-ray absorptiometry was unavailable.